Nonlinear Polytopic Systems With Predefined Time Convergence - Kumar S.; Soni S.K.; Kumar Pal A.; Kamal S.; Xiong X. (My University, 2025)
This brief deals with predefined time control for nonlinear polytopic systems. With such a control, the settling time function is uniform with respect to initial conditions of the system and can be chosen by the designer. By using the control Lyapunov function, a sufficient condition is investigated for the existence of a continuous and predefined time stable state feedback controller. The obtained sufficient condition is also necessary, such that the closed-loop nonlinear polytopic system has a robust control Lyapunov function (RCLF) for all possible parametric uncertainties. Finally, a practical system shows the efficacy of the proposed approach. © 2004-2012 IEEE.